PERGESERAN MINAT BELANJA GEN MILENIAL DAN GEN Z DI TENGGARONG - Saputra, Soni; Hana Fahleti, Widya; Dewi, Septira (Jurnal GeoEkonomi, 2025)
This study aims to analyze the differences in shopping preferences between Millennials (born 1981-1996) and Generation Z (born 1997-2012) in Tenggarong District. The research focuses on four main variables influencing purchasing decisions: cultural, social, personal, and psychological factors. A descriptive quantitative approach was employed, involving 200 respondents, consisting of 100 Millennials and 100 Generation Z individuals. Data were analyzed using the Mann-Whitney test to identify significant differences between the two groups. The findings indicate no significant differences in shopping preferences between Millennials and Generation Z across all variables examined. Although there were differences in the Mean Ranks, the p-values for cultural (0.154), social (0.132), personal (0.923), and psychological (0.300) variables were above 0.05. This demonstrates that the shopping preferences of both generations are generally similar, despite minor variations in how they access information or are influenced by trends. Factors such as ease of online shopping, trust in e-commerce platforms, and motivation to secure discounts and promotions are the main reasons for the similarities in shopping behavior between the two generations. This study provides valuable insights for businesses to design effective marketing strategies by aligning their approaches with the digital preferences and practical needs of both generations.